Energy - "Snedden, Robert" (Belitha Press Ltd: London, 1995)
This book follows the search for what an understanding of energy is, from the Ancient Greek philosophers to the great scientists of the twentieth century. It also looks at how science might help to meet our future energy needs
Keywords: Science - Book